Analysis of the Possibilities for Improving the Environmental Legislation of Kazakhstan - Buribayev, Yermek; Khamzina, Zanna; Suteeva, Canzada; Yermukanov, Yerkin; Turlykhankyzy, Kuralay; Kuttygalieva, Anarkhan (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
The study describes the results of a study of environmental problems that limit socio-economic development in Kazakhstan. Changes in legislation, management decisions, and strengthening of control over compliance with environmental standards are proposed. The article examines the gaps in the legislative regulation of environmental safety and the policy at the national level. The recommendations outlined in the research will create conditions for ensuring a higher level of environmental protection, introduce a more effective system for the prevention and control of pollution and waste management, which will inevitably lead to a significant step-by-step improvement in the quality of the environment in the medium and long term, and as a result - to reduce the levels of morbidity and mortality, loss and decrease in the working capacity of the population caused by environmental pollution. Such positive social consequences will help reduce the losses in GDP associated with the above factors.